Fetal and Neonatal Deaths Resulting from Chikungunya Virus Infection During Pregnancy: A Case Series - Monte ACP; Lacerda HR (International Medical Case Reports Journal)
Ana Cristina Pedrosa Do Monte,1,2,* Heloisa Ramos Lacerda1,3,* 1Department of Tropical Medicine, Center for Medical Sciences, Federal University of Pernambuco, Recife, Pernambuco, Brazil; 2I Regional Health Management of the State of Pernambuco Health Department, Epidemiologic Surveillance, Recife, Pernambuco, Brazil; 3Department of Clinical Medicine, Faculty of Medical Sciences, University of Pernambuco, Recife, Pernambuco, Brazil*These authors contributed equally to this workCorrespondence: Ana Cristina Pedrosa Do Monte, Department of Tropical Medicine Hospital Das Clínicas, Block a - Ground Floor of HC/UFPE Prof. Moraes Rego Avenue - s/N. 50670-901, University City, Recife, Pernambuco, Brazil, Tel +55 81 98662-3351, Email anacristina.monte@ufpe.brPurpose: We report maternal outcomes, fetal and neonatal deaths resulting from chikungunya virus (CHIKV) infection during pregnancy, addressing clinical manifestations, complications and laboratory changes.Patients and Methods: This case series included four pregnant women infected with the chikungunya virus during gestation, three fetal deaths, and two neonatal deaths confirmed as resulting from maternal-fetal transmission, during an epidemic in 2015 and 2016, in the state of Pernambuco, Northeastern Brazil. Laboratory and clinical-epidemiological criteria were applied to confirm the infection.Results: All the pregnant women were symptomatic with an onset of symptoms from the first trimester of pregnancy until 4 days after birth, with the infection confirmed by laboratory and clinical-epidemiological criteria. Among the fetal deaths, changes in the brain were the most prominent (softening and autolysis). In the neonatal deaths, there were signs of acute suffering, and low Apgar, in addition to the manifestation of severe disease with skin hyperpigmentation, limb edema, and encephalitis.Conclusion: We demonstrate the rare, although possible, occurrence of fetal death due to maternal CHIKV infection at any stage of pregnancy, as well as the risk of vertical transmission during birth, resulting in neonatal mortality. We would suggest that during epidemics this diagnosis should be considered in fetal and neonatal deaths of mothers with symptoms suggestive of chikungunya.Keywords: chikungunya virus, vertical transmission, fetal death, infant mortality